2013
DOI: 10.1370/afm.1469
|View full text |Cite
|
Sign up to set email alerts
|

Telephone Outreach to Increase Colon Cancer Screening in Medicaid Managed Care Organizations: A Randomized Controlled Trial

Abstract: PURPOSE Health Plans are uniquely positioned to deliver outreach to members. We explored whether telephone outreach, delivered by Medicaid managed care organization (MMCO) staff, could increase colorectal cancer (CRC) screening among publicly insured urban women, potentially reducing disparities. METHODSWe conducted an 18-month randomized clinical trial in 3 MMCOs in New York City in 2008-2010, randomizing 2,240 MMCO-insured women, aged 50 to 63 years, who received care at a participating practice and were ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
69
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(73 citation statements)
references
References 35 publications
(45 reference statements)
2
69
1
1
Order By: Relevance
“…In addition, consistent with Dietrich et al who showed that leadership stability was key to success in CRC screening at community health centers, we found that several STOP CRC health centers experienced turnover in key staff positions within the first year of implementation [2]. These findings reinforce the need for health centerand clinic-level data when conducting pragmatic trials and suggest that characteristics of leadership, practice experience, population served, and overall stability need to be recorded.…”
Section: Original Researchsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, consistent with Dietrich et al who showed that leadership stability was key to success in CRC screening at community health centers, we found that several STOP CRC health centers experienced turnover in key staff positions within the first year of implementation [2]. These findings reinforce the need for health centerand clinic-level data when conducting pragmatic trials and suggest that characteristics of leadership, practice experience, population served, and overall stability need to be recorded.…”
Section: Original Researchsupporting
confidence: 89%
“…Murray and colleagues noted specific challenges in partnering with primary care clinics, which may shut down unexpectedly or fail to implement electronic medical records (EMRs) or other tools on a timeline needed to fulfill the research requirements [1]. Dietrich et al showed that leadership instability threatened the success of a colorectal cancer (CRC) screening program at a community health center [2]. These factors and others may distract focus from research initiatives, which can influence the consistency with which a pragmatic intervention is delivered.…”
mentioning
confidence: 99%
“…Prior studies have shown that clinical interventions can improve overall CRC screening, 10,13,17,31 and be effective in vulnerable populations. 11,12,14,15,18,20,21,32 A recent study from our research group showed that culturally tailored patient navigation for CRC screening in a community health center eliminated disparities in CRC screening in Latinos and nonEnglish speakers in the health center, but paradoxically created a disparity in vulnerable patients receiving care in other practices within the primary care network. 16 In the current study, by integrating both health IT and a system-wide population management workforce, we demonstrated that it is possible to improve both quality and equity at the same time in a large healthcare delivery system.…”
Section: Discussionmentioning
confidence: 98%
“…4,5 Previous studies have demonstrated that several approaches for increasing overall CRC screening and reducing disparities in CRC screening are possible, such as mailed interventions, telephone outreach, and patient navigation. [10][11][12][13][14][15][16][17][18][19][20][21] However, it is unclear whether a pragmatic intervention targeting screening in large healthcare delivery systems with diverse practice types can simultaneously achieve these twin aims of quality and equity improvement. Programs targeting population-level screening rates may actually increase disparities if they are more successful in well-off groups, 13 while interventions meant to improve equity may not increase overall screening rates.…”
Section: Discussionmentioning
confidence: 99%
“…They examine both the reach and outcomes of a telephone outreach intervention designed to increase colorectal cancer screening among publicly insured urban women, delivered by Medicaid Managed Care Organization staff. 7 Safety is an important and underevaluated outcome in primary care practices. Hoffmann et al evaluate the impact of multiple factors on perceptions of a safety climate in primary care practices.…”
mentioning
confidence: 99%